Towards an Inclusive Society: Review of Google Trends Data of User Interest in the Deaf Comparing to the Blind and the Disabled - Raišienė, Agota Giedrė; Gardziulevičienė, Laura; Raišys, Simonas Juozapas; Selmistraitis, Linas (Socialinė teorija, empirija, politika ir praktika, 2021)
The COVID-19 pandemic has brought great difficulties for the deaf, the blind and people with disabilities in general, in addition to the difficulties of everyday life. This study aims to examine the public interest in the social integration of the deaf and hard of hearing community during the pandemic and the pre-pandemic period in the context of an inclusive society. The empirical study is based on the analysis of statistical data provided by Google Trends, which is a big data analysis, relative measurement and information visualisation tool that allowed to get insight on gaps and inconstancy of information seekers’ interest within categories of science, people and society, law and government, and health. The study encourages researchers and social policy makers to pay extra attention to the social inclusion of the deaf, which, according to the research data, worsened during the pandemic more than other groups of the disabled.